Reasonable Arrangement of High-Level Orientation Extraction Boreholes of Pressure Relief Gas in Overlying Strata under High-Strength Fully Mechanized Mining in Low-Gas-Thick-Coal Seam - Han Gao; Xuanping Gong; Xiaoyu Cheng; Rui Yu; Hui Wang (Shock and Vibration)
In order to solve the problem of pressure relief gas control under high-strength fully mechanized top-coal caving in low-gas-thick-coal seams, this paper studies the evolution of overburden structures and the distribution characteristics of fissure fields during the initial and stable period of working face by physical simulation and numerical analysis. The mathematical model of coupling between mining fracture field and pressure relief gas field is established. The results reveal the distribution characteristics of pressure relief gas field that considers mining-induced fissure field. According to the distribution of mining gas accumulation area, the high directional long boreholes have been put forward to control the pressure relief gas in goafs, and the effect has been tested. The results show that the initial pressure and three periodic pressures occurred from the cutting hole to 135 m in the initial mining period of the working face. The height of collapse zone developed to 22 m, and fracture height developed to 75 m. The development height of caving zone is stable at 25∼27 m, and the development height of fissure zone is stable at 75∼95 m. The process and distribution of pressure relief gas flow in goaf are obtained by solving the numerical model of pressure relief gas flow in mining fissure field. The gas accumulation area is located within 25∼55 m from return laneway and 25∼50 m from the roof of coal seam. After the implementation of high directional long drilling gas drainage technology in the initial mining period and the stable mining period, good results have been obtained in the gas control, where the average concentration of gas extraction is 5.8%, the average gas flow rate is 0.71 m3/min, and the gas concentration in upper corner and return air is less than 0.8%. The results can provide a reference for pressure relief gas control under similar conditions.